The Diversity of Freshwater Fish Species in Way Sindalapai River, Liwa Botanical Garden, West Lampung - Juriani Juriani; Gregorius Nugroho Susanto; M. Kanedi; Suratman Suratman (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2020)
The diversity of freshwater fish in Way Sindalapai River is quite abundant but there has not been much study on the diversity of fish in Way Sindalapai River. This study aims to determine the diversity of freshwater fish species in Way Sindalapai River, Liwa Botanical Garden. The study began with a preliminary survey with a purposive sampling method and sampling was carried out at 3 sampling locations. The tools used in this study include fishing nets (gill nets), fishing rods, scoop, traditional fishing gear (raas), Global Positioning System (GPS), rulers, and cameras. The sampling points include upstream, middle, and downstream areas. The method used in sample identification is by measuring the morphometry of the samples directly at the sampling location which includes total length, standard length, head length, and height, and collection of fish samples photos. Research parameters and data analysis include environmental factors, the diversity index, the evenness index, and the dominance index. The results showed that 170 fishes were found, 8 species, 2 families, and 4 genera. The fish diversity index in the Way Sindalapai river is included in the medium category from the Shanon-Wiener index calculation results, starting from the upstream, middle, downstream, respectively 1.37; 1,34 and 1,22. Evenness index at all locations are included in the low category from the Shannon-Evenness index calculation results, respectively 0.16; 0.14; and 0.12. The dominance index at all locations is included in the low category based on Simpson's dominance index, which has a value of 0.35; 0.32; and 0.28. Based on the conservation status of the IUCN Red List, ichthyofauna in the Way Sindalapai river is 5 species of low risk (least concern) namely Barbodes microps (wader goa), Rasbora bunguranensis (seluang), Barbodes binotatus (wader cakul), Thynnichtys thynnoides (lumoh), Channa striata (bogo). One species that is critically endangered is Rasbora tawarensis (depik), and two species are lacking information (data deficient) namely Rasbora sumatrana (seluang), and Rasbora semilineata (seluang)